Anisotropic plasmonic nanostructures for colorimetric sensing. (June 2020) - Zeng, Jingbin; Zhang, Yu; Zeng, Teng; Aleisa, Rashed; Qiu, Zhiwei; Chen, Yuzhu; Huang, Jiankun; Wang, Dawei; Yan, Zifeng; Yin, Yadong
Graphical abstract: Overview of anisotropic plasmonic nanostructures as colorimetric. sensors. Highlights: Colorimetric detection is extremely important for various applications where instant and convenient read-out is needed. Anisotropic plasmonic nanostructures can benefit the development of colorimetric sensors with better performance. High-performance colorimetric sensors can be fabricated using anisotropic plasmonic nanostructures of various shapes. Anisotropic plasmonic nanostructures can be used to design smart sensors that respond to external stimuli. Abstract: Colorimetric detection is important for various applications where instant and convenient read-out is needed. Because of their fascinating optical properties, plasmonic nanostructures have inspired numerous colorimetric detections for environmental contaminants, biomolecules, and pharmaceuticals. The underlying mechanism of these colorimetric sensors is that the introduction of analytes can alter the distance, spatial arrangement (orientation), size, morphology, or composition of plasmonic nanostructures, inducing distinguishable changes of spectra and color. In this review, we focus our discussion on the colorimetric detection involving anisotropic nanostructures such as nanorods, nanoplates, nanoflowers, nanobipyramids, nanoframes, and nanocubes, which exhibit many unique advantages compared to their isotropic counterparts. In addition to illustrating the design principles, sensing mechanisms, and applications of these anisotropic nanostructures-based colorimetric methods, we also discuss smart plasmonic sensors based on anisotropic nanomaterials that are used to detect external stimuli such as temperature, pH, light, magnetic field, and mechanical force.